Pengenalan Universitas Negeri Padang sebagai Upaya Memotivasi Siswa SMA Negeri 1 Payung Sekaki Melanjutkan Pendidikan ke Perguruan Tinggi - Indah Muliati; Gyska Novenia Devin; Ghandy arrizky; Sri Bunga Nasution; Nurhasanah Nurhasanah (Jurnal Pendidikan Sosial Dan Konseling, 2026)
The interest of high school students in pursuing higher education remains a concern, particularly in areas with limited access to information. A lack of understanding regarding admission pathways, study programs, and scholarship opportunities often influences students’ decisions after graduation. Therefore, this activity was conducted through a Community Service Program (KKN) aimed at introducing Universitas Negeri Padang (UNP) while encouraging students of SMA Negeri 1 Payung Sekaki to pursue higher education. The activity employed an educational and interactive approach, including presentations, discussions, and question-and-answer sessions. Data were collected through observation and direct interaction with students during the activity. The results indicate an improvement in students’ understanding of higher education, particularly regarding admission pathways and available study programs. In addition, students demonstrated a more positive attitude and increased interest in continuing their education. In conclusion, this socialization activity can serve as an effective alternative to enhance students’ motivation and readiness in planning their future education.